The Influence of Parenting and Parental Education Level with Social-Emotional Development on Early Language Development in Kindergarten in Murung Raya Village, Banjarmasin - Novrianti, Pravita Rosa; Novitawati, Novitawati; Sari, Nina Permata (Journal of English Language and Education, 2025)
This study highlights the vital role of socio-emotional and language development in early childhood as key foundations for later success. It investigates the influence of parenting styles and parental educational attainment on these developmental aspects among children at Murung Raya Kindergarten, Banjarmasin. Using a quantitative explanatory design and path analysis, data were collected from 173 parents through validated Likert-scale questionnaires. Results showed that parenting style significantly influenced language (β=0.253; p0.05) and socio-emotional development (β=0.622; p0.05), while parental education also had significant effects on both domains. Socio-emotional development strongly predicted language outcomes (β=0.578; p0.05) and mediated the relationships between parenting style and language development (Sobel = 6.674; p0.05), and parental education and language development (Sobel = 4.832; p0.05). These findings underscore the importance of supportive parenting and educational backgrounds in promoting holistic early childhood development and highlight the value of family-based interventions.